SeMAMPAN organised a Forum Rare Earth - UMP, PNC
More than 300 Universiti Malaysia Pahang (UMP) undergraduates attended a forum titled, `Rare Earth Technology: Perception and Fact’ to know more about the mineral including the processing and developing aspects as well as issues relating to the construction of a rare earth refinery plant by Lynas Corporation Sdn. Bhd. in Gebeng.